Discursive dimensions of the EU Referendum 2016 press coverage in Portugal - Simões-Ferreira, Isabel (2021)
The chapter explores the coverage of Brexit by three Portuguese newspapers, Correio da Manhã, Público and Expresso, between 4 June and 4 July 2016. From a methodological point of view, critical discourse analysis was used to analyse the way in which Portuguese journalists and columnists represented the question of political agency, namely i) the degree of prominence and framing power of each of the British actors involved in the referendum ‘battle’; ii) the interpersonal relation/evaluative attitude at European level of the opposing social actors, that is, on one side the ‘doers’ (David Cameron, Boris Johnson and Nigel Farage) and, on the other, the ‘done-tos’ (particularly the EU) in the process. The study revealed that the emphasis on the confrontational framework (UK versus EU) effaced the importance of the intraparty power struggle among the Tories; it blurred the peculiar nature of the so-called British ‘awkwardness’ in relation to the process of European integration; and it recentred the reader’s attention even more vigorously on the struggle between the sovereign will of a nation state and the supranationalism of the European project to the point that the EU ended up being constructed as ‘Other’. The double representation to which the EU is subjected, figuring simultaneously as passive agent, the recipient of the action triggered by David Cameron, and active agent, being responsible for the process that led to the victory of Brexit, is indissociable from the Portuguese recontextualisation of the theme and its left-right politicisation as a result of the austerity policies imposed on Portugal and the EU’s much publicised lack of solidarity towards the indebted countries of Southern Europe.